Evaluación a nivel de laboratorio de la eficiencia de un inhibidor de arcillas y un controlador de filtrado mediante nanotecnología para la formulación de fluidos base agua en el Campo Pendare (2020)
Pendare Field is currently operated by Tecpetrol Colombia S.A.S and presents two main problems while drilling 8 1/2" well section: the first one is clay swelling in even units of Carbonera Formation and Leon Formation, which generate a size hole reduction and the second ones are microfracturated shales in even units of Carbonera Formation, specially in C6 unit; causing instability and size hole increase. Both problems under their own effects, incresasing the number of cuttings in the well and carrying to a bit balling and a consequent stuck pipe event. These problems force to the operating company to use cleaning pills for removing cutting, causing adicional engineering cost in addition to increase operation times. Based on the fact that the current drilling fluid has a low performance, it is important to evaluate at laboratory-level the efficiency of a clay inhibitor and a filter controller using nanotecnology for water-based fluid formulation for 8 1/2" section in Pendare Field.